Penerapan Mobile Learning Dalam Mendukung Efektifitas Pembelajaran Online - Rian Farta Wijaya (STMIK Budi Darma, 2023)
The Covid-19 pandemic has caused a change in the learning and teaching process in Indonesia. The previous offline learning and teaching process has shifted to online. This change aims to prevent the spread of Covid-19. This change has necessitated the use of e-learning in the online learning and teaching process. E-learning is a medium used to deliver teaching materials from lecturers to students online. However, the use of e-learning in the online learning and teaching process is not the most suitable choice. This is because e-learning requires an internet connection and is usually more compatible when accessed through a laptop or computer rather than a smartphone. The requirements related to internet connectivity and compatibility have resulted in low mobility for students and lecturers in the learning and teaching process. They are unable to access the learning and teaching process anytime and anywhere when they are in a location without internet access or without a computer or laptop. Therefore, it is necessary to design and develop an e-learning platform specifically targeted for Android smartphones. This development is commonly referred to as mobile learning, which can be created using Android Studio. Mobile learning consists of several important pages such as login, register, class access, learning materials, and assignments. With the implementation of mobile learning, it is hoped that lecturers and students will be able to access the learning and teaching process anytime and anywhere through mobile learning